Feasibility of Home-Based Pulmonary Rehabilitation of Pediatric Patients with Chronic Respiratory Diseases - Da Yeong Kim; Young Hoon Mo; Kun Woo Kim; Sae Mi Hong; Arum Park; Baek Hee Jang; Seung Hak Lee; Joon Hee Lee; Jisun Yoon; Jinho Yu; Eun Jae Ko (MDPI AG, 2024)
Background and objective: Chronic respiratory diseases in children deteriorate their daily life due to dyspnea and reduced lung function. We aimed to evaluate the feasibility of home-based pulmonary rehabilitation in pediatric chronic respiratory diseases. Methods: This prospective, single-arm, cohort study included children with chronic lung disease. They were instructed to perform home-based pulmonary rehabilitation 30 min/session, three sessions/week for three months. Pulmonary function test (PFT) using spirometry, respiratory muscle strength (RMT), cardiopulmonary exercise test (CPET), 6 min walk test (6MWT), dyspnea questionnaires, speech evaluation, and pediatric quality of life inventory (PedsQL) were assessed pre- and post-pulmonary rehabilitation. Compliance and satisfaction of the program were also evaluated. Results: Twenty children (mean age: 11.2 ± 3.1 years) with chronic respiratory diseases without cardiopulmonary instability participated. The overall compliance was 71.1% with no related adverse events. After pulmonary rehabilitation, forced expiratory volume in one second (FEV1), peak expiratory flow (PEF), RMT, 6MWT, dyspnea questionnaire, speech rate, and PedsQL (child) significantly improved (p < 0.05), particularly better in the FEV1 < 60% group than in the FEV1 ≥ 60% group and in the high-compliance group (compliance ≥ 50%) than in the low-compliance group (compliance < 50%). Conclusions: Home-based pulmonary rehabilitation for children with chronic lung disease was feasible with high compliance and effective in terms of objective functions, subjective dyspnea symptom, and quality of life.